IMPLEMENTASI PROGRAM MERDEKA BELAJAR BAGI KEPALA SEKOLAH SD SMP DAN PENGAWAS: Implementation Of The Independence Of Learning Program For Elementary, Junior High School Principles And Supervisors - R.A. Zubaidah; Yohanes Susanto; Ujang Ujang; M Bambang Purwanto (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The 2013 curriculum change to the elementary and junior high school levels' most crucial independent learning curriculum calls for a thematic integrative learning approach where students are invited to see, pay attention, and observe their surroundings and are no longer focused on rote learning. This training's objectives are to develop student competency in the areas of knowledge and skills as well as the understanding of teachers, principals, and supervisors on the implementation of the independent learning curriculum. Thirty school administrators and supervisors participated in this seminar. The program's outcomes demonstrated that the participants, who were principals and supervisors of schools in the city of Palembang, were able to comprehend the training materials properly both before and after the training. It is hoped that this training would be provided to all teachers so that they can comprehend how to execute the autonomous learning curriculum and enhance their capacity to do so in accordance with their unique circumstances.